Ansiedade e baixo nível motivacional associados ao fracasso na cessação do tabagismo - Pawlina, Maritza Muzzi Cardozo; Rondina, Regina De Cássia; Espinosa, Mariano Martinez; Botelho, Clóvis (Instituto de Psiquiatria da Universidade Federal do Rio de Janeiro, 2014)
Objective To analyze the association between the socio-demographic characteristics, smoking status, the degree of motivation, the degree of anxiety, depression and stress with failure in patients of a smoking cessation program. Methods Cross-sectional study conducted with patients who sought the smoking cessation program in Cuiabá/MT, Brazil. All the smokers enrolled in the initial phase of these programs, from May to August 2012, were invited to participate in this study, totalizing 216 patients. The instruments used were Socio-demographic Profile Questionnaire, Fagerström Test (FTND), URICA, Beck Anxiety Inventory (BAI), Beck Depression Inventory (BDI) and Lipp Stress Symptoms Inventory (LSSI). The data were entered twice into Epidata, version 3.1 program and for the data analysis Poisson regression model was used. Results Associations of the therapeutic failure with the following variables were found: young age group (RP = 1,68 IC 95% 1,11-2,56); shorter time of tobacco use (RP = 1,32; IC 95% 1,09-1,61); higher cigarette consumption/day (RP = 1,24; IC 95% 1,01-1,52) and lower level of motivation (RP = 1,55; IC 95% 1,04-2,30). In the final model (RPa), the following variables were associated with failure: shorter time of smoking (RPa 1,53; IC 95% 1,07-2,32), higher smoking burden (RPa 1,48; IC 95% 1,12-1,95), low level of motivation (RPa 1,58 IC 95% 1,07-2,32) and high level of anxiety (RPa 1,22; IC 95% 1,01-1,48). Conclusion: Low motivational level (Contemplation and Pre-contemplation), high level of anxiety (moderate/severe), shorter time of tobacco use, high tobacco intake are associated with therapeutic failure.

Objetivo Analisar a associação entre as características sociodemográficas, status do tabagismo, grau de motivação, nível de ansiedade, depressão e de estresse com o fracasso em pacientes de um programa de cessação de tabagismo. Métodos Estudo de corte transversal realizado com pacientes que procuraram os programas de cessação do tabagismo de Cuiabá/MT, Brasil. Todos os fumantes matriculados no início desses programas, durante o período de maio a agosto de 2012, foram convidados a participar deste estudo, totalizando 216 pacientes. Os instrumentos utilizados foram o questionário Perfil Sociodemográfico, Teste de Fagerström (FTND), URICA, Inventário de Ansiedade de Beck (BAI), Inventário de Depressão de Beck (BDI) e Inventário de Sintomas de Stress de Lipp (ISSL). Os dados foram digitados duplamente em programa Epidata versão 3.1, e para análise dos dados foi utilizado um modelo de regressão de Poisson. Resultados Foram encontradas associações do fracasso terapêutico com as seguintes variáveis: faixa etária jovem (RP = 1,68; IC 95% 1,11-2,56); menor tempo de tabagismo (RP = 1,32; IC 95% 1,09-1,61); maior consumo de cigarros/dia (RP = 1,24; IC 95% 1,01-1,52) e menor grau de motivação (RP = 1,55; IC 95% 1,04-2,30). No modelo final (RPa), ficaram associadas ao fracasso as variáveis: menor tempo de tabagismo (RPa 1,53; IC 95% 1,07-2,32), maior carga tabágica (RPa 1,48; IC 95% 1,12-1,95), baixo nível de motivação (RPa 1,58; IC 95% 1,07-2,32) e alto nível de ansiedade (RPa 1,22; IC 95% 1,01-1,48). Conclusão Baixo nível motivacional (Contemplação e Pré-contemplação), alto nível de ansiedade (moderado/grave), menor tempo de tabagismo e alta carga tabágica estão associados ao fracasso terapêutico.
Anxiety and low motivational level associated with the failure in smoking cessation
Keywords: Ansiedade; motivação e tabaco; Anxiety; motivation and tobacco